2010
DOI: 10.3109/01942630903337478
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Therapist's Role in Care Coordination between Medical and Early Intervention Services

Abstract: This study explored perspectives of therapist's role in care coordination between early intervention (EI) and medical services, and identified strategies for improving service delivery. Fifty adults participated in one of six focus groups. Participants included parents, pediatricians, and therapists working in hospital and EI programs. Structured guiding questions were used to obtain participants' perceptions. Transcript analysis included open code identification, axial code grouping, and constant comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The findings of qualitative study of seven occupational therapists' experiences with the model suggested it may hold promise toward overcoming barriers to collaboration (Campbell, Missiuna, Rivard, & Pollock, 2012). Ideishi et al (2010) have examined perspectives of therapists' roles in care coordination between medical and early intervention services for children with special healthcare needs. The authors call for family-centered care perspectives and strategies to improve care coordination and integration across systems.…”
Section: Implications For Practicementioning
confidence: 99%
“…The findings of qualitative study of seven occupational therapists' experiences with the model suggested it may hold promise toward overcoming barriers to collaboration (Campbell, Missiuna, Rivard, & Pollock, 2012). Ideishi et al (2010) have examined perspectives of therapists' roles in care coordination between medical and early intervention services for children with special healthcare needs. The authors call for family-centered care perspectives and strategies to improve care coordination and integration across systems.…”
Section: Implications For Practicementioning
confidence: 99%
“…39 School physical therapists also can serve as the intermediary between the educational system and the medical system and can help families negotiate both systems and understand the differences. Among the team members, physical therapists often are the most familiar with the medical system and terminology, so they are frequently called on by teachers, administrators, and parents to help interpret medical records that the school receives and communicate with health care providers.…”
Section: Roles For Physical Therapists In Care Coordinationmentioning
confidence: 99%
“…Since second-generation approaches emerged favoring transdisciplinary approaches, it is clear that physical and occupational therapists continue to fill roles on the basis of their unique training and expertise that are not shared by other EI providers (Ideishi, O'Neil, Chiarello, & Nixon-Cave, 2010). One important role identified for therapists was that of helping parents and other team members understand reports about children's health and medical status.…”
Section: Outcomes Of Second-generation Eimentioning
confidence: 99%